Labour Dynamics and Informal Cross-Border Trade in Rural Border Communities of Sarawak, Malaysia. - Leha, Saliman; Nor Hanim, Awang @ Mohd Noor; Swee Kiong, Wong (the Latin American Association of the Pope (ALAP), 2025)
This study examines the complex labour dynamics and informal cross-border trade that influence the livelihoods of rural communities in Sarawak, Malaysia, with a focus on the Pantu District of Sri Aman, Sarawak. Situated close to the border with West Kalimantan, the Bukit Kelingkang mountain range forms a natural boundary between Malaysia (Sarawak) and Indonesia (Kalimantan). For generations, economic exchanges between villages on both sides have been deeply rooted in history. The Iban people, in particular, have maintained strong patterns of migration, reciprocal trade, and familial ties that predate colonial rule. Following independence, the political division of Borneo redefined these connections, with Iban communities on either side becoming residents of Malaysia and Indonesia respectively. The research explores patterns of migration, intermarriage, informal employment, and trade practices that shape the socio-economic fabric of the borderland. Employing a mixed-methods approach, the study combines quantitative surveys of 220 rural respondents with qualitative data from 12 in-depth interviews with longhouse leaders and two local community chiefs in Pantu, Sri Aman. Quantitative findings indicate a significant dependence on Indonesian migrant labour, especially for agricultural and plantation work, due to local workforce shortages. Qualitative insights reveal the prevalence of cross-border marriages, the pivotal role of Indonesian labourers, and the informal yet vital trade exchanges that sustain daily life. The study concludes that rural border communities in Sarawak rely heavily on flexible and informal economic arrangements to navigate socio-economic challenges. By examining these interconnected dynamics, the research contributes to a deeper understanding of rural livelihoods in borderland regions, highlighting the resilience and adaptability of communities facing structural limitations and evolving cross-border interactions.